Sustainability and duration of early central places in prehispanic Mesoamerica - Feinman, Gary M.; Carballo, David M.; Nicholas, Linda M.; Kowalewski, Stephen A. (Frontiers in Ecology and Evolution, 2023)
During the last millennium BCE, central places were founded across many regions of western (non-Maya) Mesoamerica. These early central places differed in environmental location, size, layout, and the nature of their public spaces and monumental architecture. We compare a subset of these regional centers and find marked differences in their sustainability--defined as the duration of time that they remained central places in their respective regions. Early infrastructural investments, high degrees of economic interdependence and collaboration between domestic units, and collective forms of governance are found to be key factors in such sustainability.